An exploration tool for quality analysis in targeted sequencing experiments - Merino, Gabriela Alejandra (2015)
Amplicon Exome Sequencing allows focusing on exonic regions of a small group of genes. The overall aim is to inquire sequenced regions about the occurrence of mutations, single nucleotide polymorphisms, insertions and deletions, trough Variant Calling analysis. The first steps include se-quencing, followed by alignment. Prior to further analysis, it is crucial to evaluate how well the sequencing run was achieved, as well as the quality of the carried experiment. At present, there are several open access tools to perform these tasks. But, most of them were designed for whole genome data. Hence, they are computationally expensive to just analyze a small group of genes. In addition they only offer limited visualization capabilities. Here, we proposed a light-weight amplicon se-quencing exploration tool for fast visualization and experiment quality control. The tool was developed under R language and can be executed in parallel in order to provide fast and accu-rate quality control results within a few minutes. The article presents the tool implementations and capabilities. Finally, we show its application on real amplicon sequencing data.